Some dialect characteristics in selected local Slovenian dialect texts of the Littoral and Lower Carniolan dialect groups - Bilavčić, Mateja; Zupančič, Špela (Jezikoslovni zapiski, 2018)
This article uses texts about spring chores to present selected local dialects of the Littoral dialect (Sovodnje, Karst dialect; Lokev, Inner Carniolan dialect) and the Lower Carniolan dialect group (Borovnica and Ambrus, Lower Carniolan dialect; Globočdol and Šentrupert, Eastern Lower Carniolan subdialect). Dialect consonant features, special morphological features, and interesting lexemes are examined synchronically and compared with standard Slovenian.